Authentication Using Improved Image Based OTP - Gupta, Shweta; Gupta, Prateek; Ranjan, Amit (International Journal of Computer Sciences and Engineering, 2025)
Everything in our digital life requires an authentication mechanism to establish the identity of the user and protect his/her privacy. Since passwords are the most common form of authentication, our aim is to provide an alternative form that is not susceptible to the security risks and problems associated with passwords. However, the password may be foreseeable because it should be easy for users to memorize. Thus, an rival could get the passwords of users by brute-force attack in a short period of time. Two-Factor Authentication (TFA) can be used as a antidote to this weakness. One Time Password is mostly used authentication method now days. Our proposed idea is to enhance the security level of One Time Password by using improved and more secure image based OTP. In this method text fields are encrypted with image as key string to produce OTP. Proposed method keep resistance against token theft, man in the middle attack, reply attacks etc.